Republic of Equatorial Guinea : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report evaluates the Observance of Standards and Codes on Fiscal Transparency for the Republic of Equatorial Guinea. Equatorial Guinea needs to improve transparency in many of the important elements of the Code of Good Practices on Fiscal Transparency, but a basis is being established to implement key fiscal transparency practices. An improved legal framework for fiscal management, in harmony with regional partners, has been put in place, notably through the 2003 Public Finance Law and the 2004 Tax Code. The authorities at the highest level have also indicated their commitment to improving fiscal transparency.